PERANGKAT PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Fuja Sabella (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2023)
Islamic religious learning training as one of the subjects in schools or madrasas which demands Islamic life values, should be pursued through good learning arrangements, so that it can have an impact on decision making, choices and improving students' lives. Middle School PAI learning tools refer to a set of tools, plans, materials and strategies used by teachers (educators) to provide knowledge about the Islamic religion to students. PAI learning tools are planned so that the experience of Islamic education in schools can run in an organized, interesting and successful manner. The aim of the PAI learning tools is to achieve different learning outcomes which include students' understanding in interpreting the lessons, values, history and practices of the Islamic religion, as well as helping them in assimilating the characteristics of Islam into their daily lives. daily routine.